Understanding the World Economy in Terms of Networks: A Survey of Data-Based Network Science Approaches on Economic Networks - Emmert-Streib, Frank; Tripathi, Shailesh; Yli-Harja, Olli; Dehmer, Matthias (Frontiers in Applied Mathematics and Statistics, 2018)
The purpose of this paper is to survey studies for estimating and analyzing different types of economic networks We focus on data-based approaches that allow the direct estimation of the networks from empirical data without the need of relying on theoretical assumptions. Due to the fact that there is a large variety of different economic networks, e.g., interbank, investment, director, ownership, financial, product or trade networks, we present a systematic categorization of these by the meaning of the “nodes” within these networks. These can correspond to banks, firms, investors, products, stocks etc. Furthermore, we review practical methods for graphically exploring such networks and discuss useful databases for obtaining the empirical data for the computational construction of economic networks.